Macrolide Efflux Genes mef(A) and mef(E) Are Carried by Different Genetic Elements in Streptococcus pneumoniae - Del Grosso, M. (American Society for Microbiology, 2002)
Susceptibilities to macrolides were evaluated in 267 Streptococcus pneumoniae isolates, of which 182 were from patients with invasive diseases and 85 were from healthy carriers. Of the 98 resistant isolates, 20 strains showed an M phenotype and carried mef. Strains that carried both mef(A) and mef(E) were found: 17 strains carried mef(A) and 3 carried mef(E). The characteristics of the strains carrying the mef genes and the properties of the mef-containing elements were studied. Strains carrying mef(A) belonged to serotype 14, were susceptible to all the antibiotics tested except erythromycin, and appeared to be clonally related by pulsed-field gel electrophoresis (PFGE). The three mef(E) strains belonged to different serotypes, showed different susceptibility profiles, and did not appear to be related by PFGE. The sequences of a fragment of the mef-containing element, which encompassed mef and the msr(A) homolog, were identical among the three mef(E)-positive strains and among the three mef(A)-positive strains, although there were differences between the sequences for the two variants at 168 positions. In all mef(A)-positive strains, the mef element was inserted in celB, which led to impairment of the competence of the strains. In line with insertion of the mef(E) element at a different site, the competence of the mef(E)-positive strains was maintained. Transfer of erythromycin resistance by conjugation was obtained from two of three mef(A) strains but from none of three mef(E) strains. Due to the important different characteristics of the strains carrying mef(A) or mef(E), we suggest that the distinction between the two genes be maintained.